Enhancing eggplant (Solanum melongena L.) yield and water use efficiency through optimized irrigation and nitrogen practices in open field conditions - Adewale Suraj, Bello (2024)
This study evaluated the interactive effects of deficit irrigation and nitrogen application on eggplant growth and yield under water scarcity in Northern Qatar (2022–2023). Two irrigation regimes were tested: full irrigation (100 %, I2) and deficit irrigation (50 %, I1), along with three nitrogen levels: 100 kg N ha−1 (F3), 70 kg N ha−1 (F2), and 50 kg N ha−1 (F1). The six treatment combinations (I1,2 + F1,2,3.) were analyzed for vegetative growth, yield components, and overall yield. Deficit irrigation (I1) increased eggplant fruit yield by 17.86 % compared to full irrigation (I2) and improved shoot height, stem diameter, and SPAD index. Nitrogen application also significantly influenced vegetative growth, with the best results seen at 50 kg N ha−1. While average fruit weight did not differ significantly across nitrogen levels, the highest fruit yield was recorded under F1 and F2 treatments. Water use efficiency (WUE) was highest under deficit irrigation (I1) at the 70 kg N ha−1 level (I1 + F2), reaching 0.41 kg ha−1 mm−1. The lowest WUE of 0.23 kg ha−1 mm−1 was observed in I2 + F2, which also had the lowest fruit yield (24.43 t ha−1). Applying 70 kg N ha−1 during deficit irrigation (I1 + F2) produced the highest fruit yield compared to other treatments, although no significant difference was found with I1 + F1. The study highlights the importance of optimized nitrogen and irrigation management for maximizing eggplant production in water-limited environments.